Evaluation of Susceptibility of Human Herpesvirus 8 to Antiviral Drugs by Quantitative Real-Time PCR - Sergerie, Yan (American Society for Microbiology, 2003)
A new in vitro system based on real-time PCR was developed for evaluation of human herpesvirus 8 susceptibility to antiviral agents. Cidofovir had the greatest inhibitory activity against HHV-8 (50% inhibitory concentration [IC(50)], 0.43 μM) followed by ganciclovir (2.61 μM), adefovir (18.00 μM), acyclovir (31.00 μM), and foscarnet (34.15 μM). The potential therapeutic efficacy for HHV-8 (i.e., peak serum drug level/IC(50)) is highest for cidofovir (167) and foscarnet (22).